The Role of Parents in Using Gadgets for Early Childhood Development - Krisna Ivarianti; Ayu Aprilia Pangestu Putri; Azainil Azainil (Universitas Al-Hikmah Indonesia, 2025)
Early childhood is a golden period in a child's development that greatly determines their future, including in terms of the use of technology such as gadgets. In the digital era, children are increasingly familiar with technological devices from an early age, so the role of parents becomes very crucial in directing the use of gadgets wisely. This study aims to describe the role of parents in the use of gadgets on the development of early childhood, with a focus on parenting strategies and their impact on the cognitive, social, and emotional aspects of children. The approach used is qualitative with a case study type of a 4-year-old child (Ananda R) in Samarinda City. Data were collected through direct observation, interviews with parents, and documentation, then analyzed using the Miles and Huberman model. The results of the study showed that the active involvement of parents is very influential in forming healthy gadget usage habits. Ananda R's parents act as guides, facilitators, motivators, and role models. Gadget use is situationally limited, always supervised, and balanced with physical activity, social interaction, and non-digital learning such as reading, playing puzzles, and outdoor activities. The content presented is educational and selectively selected. This support has been proven to support cognitive and social development, as well as helping children manage their emotions. This study emphasizes the importance of parental involvement in digital parenting as an effort to create a balance between the use of technology and the holistic and responsible development of children.